MOHAMMAD HATTA AND RELIGIOUS-NATIONALISM EDUCATION IN BANDA EXILE - Renyaan, Kasman (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This article describes the thinking and consistency of a figure of the National Movement, Mohammad Hatta, during his exile in Banda Naira in 1963–1942. Research uses historical methods through heuristic, critical, interpretative, and historiographic stages. The main sources used were the work of the historian's books, other reference books, observations of objects in the house of his exile, and interviews with Banda Naira people. The study found that Mohammad Hatta, during Banda Naira's exile, remained critical (non-cooperative) of colonial policy. Hatta's routine on the spice island is filled with various activities to educate the community and the young generation of Banda, ranging from reading, writing, sports, attending public wedding invitations, speaking in mosques, forming youth organizations (PERBAMU), to playing the role of setting up the